Equilibrium and Kinetic Studies of the Adsorption of Zn(II) Ions onto Natural and Activated Kaolinites - Ali Riza Kul; Necla Caliskan (Adsorption Science & Technology)
The removal of Zn(II) ions from aqueous solution was studied using natural, thermally-activated and acid-activated kaolinite samples at different temperatures. The linear Langmuir, Freundlich and Dubinin– Radushkevich (D–R) adsorption equations were applied to describe the equilibrium isotherms. The Langmuir constants for natural kaolinite were found to be negative whereas, for the other samples, the isotherm models gave a good fit. In addition, the pseudo-first-order and pseudo-second-order models were used to determine the kinetic data. The experimental data were well fitted by the pseudo-second-order kinetic model. Thermodynamic parameters such as the enthalpy (ΔH 0 ), Gibbs' free energy (ΔG 0 ) and entropy (ΔS 0 ) were calculated for natural, thermally-activated and acid-activated kaolinite. These values showed that the adsorption of Zn(II) ions onto activated kaolinite was controlled by a physical mechanism and occurred spontaneously. The process of adsorption was favoured at high temperatures, with the adsorption capacity of the acid-activated kaolinite being greater relative to that of natural and thermally-activated kaolinite at various temperatures.